(untitled) (INNOVATIVE ECONOMY, 2020)
Zinchenko O.A., Gorska S.M., Zinchenko D.S. THEORETICAL AND METHODOLOGICAL BASES OF IMPROVING THE MANAGEMENT OF THE SYSTEM OF IMPROVING THE QUALITY OF HIGHER EDUCATION INSTITUTIONS Purpose. The aim of the article is substantiation and development of theoretical and methodological bases for improving the management of the system of improving the quality of higher education institutions. Methodology of research. Methods of dialectical cognition, analytical information processing, methods of comparison, grouping, graphic methods, etc. are the methodological basis for the development of theoretical and practical provisions. The following methods are used in the study: structural and logical analysis – to build the logic and structure of work; system analysis and synthesis – to study the essence of the subject of study; system approach – to improve the system and targeted approach to the management of the system of improving the quality of higher education institutions. Findings. Peculiarities of interpretation of the concept of quality system of activity of higher education institutions are investigated. The conceptual bases of management of the system of improving the quality of higher education institutions are substantiated. Theoretical and methodological bases of management of the system of improving the quality of higher education institutions are revealed and the strategy of such management is improved. The components of the system of measures and procedures in the process of ensuring the quality of higher education are presented. Originality. Provisions for the management of the process of ensuring the quality of higher education institutions in terms of developing formalized: the concept, algorithm and system of such management from a theoretical and methodological standpoint in order to more clearly implement in practice. The symbiosis of modern innovative technologies of educational process management with emphasis on effective use of intellectual capital of all employees of higher education institutions will help to improve the quality of their activities. Practical value. The theoretical and methodological principles proposed in the work on the quality management system of higher education institutions are designed to enhance the competitiveness of domestic education and can be applied by higher education institutions of all forms of ownership. Key words: quality of education, institution of higher education, quality of activity of institution of higher education.